The Effect of Religiosity, Profit Los And Sharing on Consumer Trust and Intention to Financing in Islamic Bank - Rizal Ula Ananta Fauzi; Arman ahmad; Zaki bahrun Niam; Izian Idris; Isabela indah Puspita Ningrum (Institut Agama Islam Negeri Kendari, 2021)
With a majority Muslim population, Indonesia has a good market share for Islamic banks. The existence of conventional banks becomes a competition to determine the strategy of Islamic bank managers. This study aimed to examine the effect of honesty and profit-sharing on trust mediation on consumer intentions. This study uses SPSS analysis and the Sobel test to see the role of mediation. Samples were taken as many as 384 respondents from the Muslim community. The analysis results obtained that religiosity significantly affects consumer trust and intentions. Profit and loss sharing significantly impacts confidence and does not affect consumer intentions. Trust can provide a significant mediating role. In terms of increasing the factors that influence consumer intentions, company managers must build consumer trust, the opportunity for a religious community to become a potential target market.